Antioxidant Potential, Quantification of Phenolics and Flavonoids, and Characterization of Secondary Metabolites of Stem Methanol Extract of Mitrella kentii (Blume) Miq. Using LC-MS/MS Analysis - Siregar, Astri Rozanah; Sinaga, Ernawati (Journal of Tropical Biodiversity, 2025)
Mitrella kentii (Blume) Miq., a wild plant from the Annonaceae family, naturally grows in the peat swamp forests of Kalimantan, Indonesia. Known as Black Bajakah among the Dayak Ngaju community in Central Kalimantan, its stems have traditionally been used to treat various ailments and restore stamina during forest work. This study aimed to identify secondary metabolites in the methanolic extract of M. kentii stems and to explore its potential for medicinal applications and drug discovery. LC-MS/MS analysis was conducted using a C18 column on the Waters Acquity UPLC system, with electrospray ionization in positive and negative ion modes. Compound identification employed the UNIFI data processor with the Waters Traditional Medical Scientific Library database. The analysis revealed five bioactive compounds: d-Lirioferine (lirioferine), isosinomenine, N-(1,7-Dimethoxy-phenanthren-2-yl)-acetamide, scoulerine, and yuanhunine, all with documented biological activities. Quantitative analysis showed the extract contained 36.23% total phenols, 0.44% total flavonoids, and exhibited very strong antioxidant activity with an IC50 value of 12.06 ppm. These results support the traditional medicinal use of M. kentii and highlight its potential as a source of bioactive compounds for future pharmaceutical development.